The hospitals of London: administration, refoundation, and benefaction, c.1500-1572 - Daly, CT (1993)
This thesis studies the organisation and government of the hospitals of London in the first three quarters of the sixteenth century. Particular emphasis is laid on the changes in the network of church-affiliated hospitals during the period of the Dissolu- tion of the Monasteries, and the subsequent reorganisation of several of these institu- tions in the reign of Edward VI. Mainly through the use of the contemporary records of the hospitals and the City, the different but complementary functions of St. Bartholomew's, St. Thomas's, and Christ's Hospitals are analysed over the span of the first twenty-five years after their reorganisation. The implementation of the Elizabethan Poor Laws in 1572 is adopted as the terminus point for this study.